Effects of proanthocyanidins and caffeic acid on the structure, gelatinization, rheology, and digestion properties of fermented foxtail millet starches - Lei Chang; Yang Yao; Yueyi Dang; Yangjin Liu; Jibao Liang; Rui Li; Rui Zhang; Xiuzhu Yu; Shuang-kui Du (Food Hydrocolloids, 2026)

Exploring the mechanism of platycodon grandiflorum saponins in treating Mycoplasma pneumoniae pneumonia based on intestinal microbiota and metabolomics - Rui Shuang Ji; Yun Fei Yang; Chan Yu Wu; Zhen Jing Yang; Jin Zhao Du; Jing Huang Fu; Lin Yao; Wei Ming Wang (Food Bioscience, 2026)

Plastisphere-driven pollutant enrichment and harmful bacteria proliferation: Emerging ecological risks to Danjiangkou reservoir's water security - Tao He; Zhi-Min Xu; Le-Yi Cheng; Yi-Cai Zhang; Shuang Wang; Xiao-Yan Zhang; Xi Yang; Yu-Ting Hou; Si-Yi Wang; Xin-Yue Hu; Xin-Rui Zhou; Yong-Hong Ma; et al. (Marine Pollution Bulletin, 2026)

Overexpression of PtrPYL11 enhance drought tolerance in Populus: evidence from genome-wide identification and comparative transcriptome profiling - Shuang-Lian Deng; Shu-Ying Wei; Rui-Quan Wang; Yuan Zhang; Hao Li; Xing-Yu Liu; Xin-Ran Yu; Guan-Ru Ren; Ting Wang; Fang He (Plant Cell Reports, 2026)

Dynamic characteristics of a novel floating offshore photovoltaic system with flexible rope-net connection - De-Qing Zhang; Hong-Wei Tian; Zhi-Ming Yuan; Shuang-Rui Yu; Jun-Feng Du; Hua-Jun Li (Ocean Engineering, 2025)

Enhanced electrocatalytic oxidation of high-salinity quaternary ammonium compound wastewater using CNTs-(Ru Ir O2)/Ti Anode - Hao-Tian Liu; Han-Qing Zhao; Yi-Rui Yang; Shuang Wu; Jia-Ping Huang; Rui-Han Yu; Hongcheng Bai; Aqiang Ding; Daijun Zhang; Peili Lu (Journal of Environmental Sciences, 2025)

Deinococcus lichenicola sp. nov., A Bacterium Isolated from a Lichen Sample - Guo-Hua Chen; Lian-Shuang Xiong; Rui Yang; Shu-Ya Zuo; Qing Yuan; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

CORBES: Radiation belt survey with international small satellite constellation - Ji Wu; Li Deng; Jaan Praks; Marius Anger; Philipp Oleynik; Wojciech Hajdas; Jin-Dong Wang; Shen-Yi Zhang; Bin Zhou; Li Zeng; Jinbin Cao; David Fischer; et al. (Advances in Space Research, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Leifsonia stereocauli sp. nov., Isolated from Stereocaulon tomentosum Fr. Lichen - Shu-Ya Zuo; Lian-Shuang Xiong; Qing Yuan; Guo-Hua Chen; Rui Yang; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Portable paper-based microfluidic devices with Cu1-xAgxS NPs modification for multiplex intelligent visualized detection of adrenaline and glucose simultaneously - Huan Wang; Lihua Dong; Gina Ma; Shuang Qiu; Guiye Shan; Lijia Zhao; Yu Sun; Anni Cui; Rui Zhang; Xiaojie Liu (Analytica Chimica Acta, 2025)

Optimal declutching control of hinged multiple floating bodies - Shuang-Rui Yu; Ming Zhang; De-Qing Zhang; Zhi-Ming Yuan (Ocean Engineering, 2024)

Highly nanostructured and carboxylated wood aerogel-based adsorption membrane reconstructed by grafting of polyacrylic acid for efficient removal of heavy-metal ions - Wen He; Bairen Wei; Shuang Liang; Rui Wang; Qiulin Ji; Gangzheng Hu; Wenxuan Li; Lei He; Juan Yu; Hongfei Zhu; Kaiyin Wang (Chemical Engineering Journal, 2024)

Roundup® induces premature senescence of mouse granulosa cells via mitochondrial ROS-triggered NLRP3 inflammasome activation - Heliang Ni; Xiangdong Hu; Nannan Yang; Xiaoyang Liu; Wenyang Cai; Rui Zhong; Tiancheng Wang; Mingxi Yu; Shuang Tang (Toxicological Research, 2024)

Model predictive control of wave energy converters - Ming Zhang; Shuang-Rui Yu; Guang-Wei Zhao; Sai-Shuai Dai; Fang He; Zhi-Ming Yuan (Ocean Engineering, 2024)

Soil moisture drives the shift from selection to complementarity effect in the rainfed maize/faba bean intercropping system - Wei Wang; Meng-Ying Li; Wei Zhang; Aziz Khan; Rui Zhou; Shuang-Guo Zhu; Bao-Zhong Wang; Yu-Miao Yang; Hong-Yan Tao; Wen-Bo Li; You-Cai Xiong (Plant and Soil, 2024)

High-efficiency preparation of starch nanocrystals with small size and high crystallinity by ethanol-acid penetration and dry-heating pretreatment - Wen-Xuan Hu; Xin-Rui Hu; Fan Jiang; Yulian Zhu; Min Yang; Qin Dan; Xiuzhu Yu; Shuang-kui Du (Food Chemistry, 2024)

A polypyrrole-dopamine/poly(vinyl alcohol) anisotropic hydrogel for strain sensor and bioelectrodes - Shuang Chen; Bingyan Guo; Jiajun Yu; Zhuojun Yan; Rui Liu; Chaojie Yu; Zhongming Zhao; Hong Zhang; Fanglian Yao; Junjie Li (Chemical Engineering Journal, 2024)

Improving on mapping long-term surface water with a novel framework based on the Landsat imagery series - Ling Lan; Yu-Ge Wang; Hao-Shuang Chen; Xu-Rui Gao; Xie-Kang Wang; Xu-Feng Yan (Journal of Environmental Management, 2024)

pH-responsive ZIF-8 film-coated mesoporous silica nanoparticles for clean, targeted delivery of fungicide and environmental hazard reduction - Yingjian Ma; Yinmin Wang; Rui Zhao; Zhijie Wang; Shuang Li; Meng Yu; Sen Pang; Xinyu Guo; Yong Xu; Xuemin Wu (Journal of Environmental Chemical Engineering, 2023)

Arbuscular mycorrhiza changes plant facilitation patterns and increases resource use efficiency in intercropped annual plants - Shuang-Guo Zhu; Hai-Xia Duan; Hong-Yan Tao; Li Zhu; Rui Zhou; Yu-Miao Yang; Xiao-Lin Zhang; Wen-Ying Wang; Hao Zhu; Wei Zhang; Ren-Qing Wang; Xiu-Ping Tao; et al. (Applied Soil Ecology, 2023)

Time-optimal path planning and tracking based on nonlinear model predictive control and its application on automatic berthing - Ming Zhang; Shuang-Rui Yu; Kwang Sic Chung; Ming-Lu Chen; Zhi-Ming Yuan (Ocean Engineering, 2023)

Efficient lipid synthesis of Chlorella pyrenoidosa promoted under heavy metals from electric arc furnace slag - Qing Yu; Tian-Ji Liu; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Yu-Ran Wang; Le-Le Kang; Rui Ji; Fu-Ping Wang; Xiao-Man Wang; Bao Liu; Shuang Cai; et al. (Journal of Cleaner Production, 2023)

Canopy height, rather than neighborhood effects, shapes leaf herbivory in a tropical rainforest - Shuang Zhang; Guo‐Rui Xu; Yu‐Xin Zhang; Wen‐Fu Zhang; Min Cao (Ecology, 2023)
Factors shaping the interspecific variations in herbivory have puzzled ecologists for decades and several hypotheses have been proposed to explain interspecific variation in leaf herbivory. In a tropical rainforest in Yunnan Province, China, we collected 6732 leaves from 129 species with canopy heights ranging from 1.6 to 65.0 m above the ground. We tested the role of canopy height, the diversity, composition and structural heterogeneity of neighbors and leaf traits in shaping the interspecific variations in herbivory. Results show that leaf herbivory decreased with canopy height and specific leaf area (SLA) and increased with leaf size. However, neighboring species' diversity, composition, and structural heterogeneity showed no association with herbivory. Therefore, neither the visual apparency effect nor the associational resistance effect was detected in this hyperdiverse tropical rainforest. These findings highlight the importance of vertical structure in shaping herbivory patterns in natural communities.

Phthalate Mixture Exposure is Associated with Elevated Blood Pressure in Chinese Children: A Panel Study - Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Huihua Yang; Meng Li; Shuang Chen; Jie Yu; Qin Fang; Xuefeng Lai; Liangle Yang; Rui Zhu; et al. (Exposure and Health, 2023)

Intercrop overyielding weakened by high inputs: Global meta-analysis with experimental validation - Shuang-Guo Zhu; Hao Zhu; Rui Zhou; Wei Zhang; Wei Wang; Yi-Ning Zhou; Bao-Zhong Wang; Yu-Miao Yang; Jing Wang; Hong-Yan Tao; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2023)

Microplastics perturb colonic epithelial homeostasis associated with intestinal overproliferation, exacerbating the severity of colitis - Shuang Xie; Rui Zhang; Zhaoyan Li; Chunru Liu; Yanyu Chen; Qinghua Yu (Environmental Research, 2023)

Soil water and phosphorus availability determines plant-plant facilitation in maize-grass pea intercropping system - Shuang-Guo Zhu; Hao Zhu; Zheng-Guo Cheng; Rui Zhou; Yu-Miao Yang; Jing Wang; Wei Wang; Bao-Zhong Wang; Hong-Yan Tao; You-Cai Xiong (Plant and Soil, 2023)

Associations of urinary polycyclic aromatic hydrocarbon metabolites and blood pressure with the mediating role of cytokines: A panel study among children - Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Huihua Yang; Jie Yu; Shuang Chen; Meng Li; Qin Fang; Xuefeng Lai; Liangle Yang; Rui Zhu; et al. (Environmental Science and Pollution Research, 2022)

Identification of Ferroptotic Genes in Spinal Cord Injury at Different Time Points: Bioinformatics and Experimental Validation - Yu Kang; Qiangwei Li; Rui Zhu; Shuang Li; Xin Xu; Xuanming Shi; Zongsheng Yin (Molecular Neurobiology, 2022)

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

Gastrodin Regulates the Notch Signaling Pathway and Sirt3 in Activated Microglia in Cerebral Hypoxic-Ischemia Neonatal Rats and in Activated BV-2 Microglia - Jing Guo; Xiao-Li-Na Zhang; Zhang-Rui Bao; Xue-Ke Yang; Ling-Shuang Li; Yu Zi; Fan Li; Chun-Yun Wu; Juan-Juan Li; Yun Yuan (NeuroMolecular Medicine, 2021)

Systematic analysis of lncRNA expression profiles and atherosclerosis-associated lncRNA-mRNA network revealing functional lncRNAs in carotid atherosclerotic rabbit models - Yingnan Wu; Feng Zhang; Xiaoying Li; Wenying Hou; Shuang Zhang; Yanan Feng; Rui Lu; Yu Ding; Litao Sun (Functional & Integrative Genomics, 2020)

The N-terminal and central domain of colicin A enables phage lysin to lyse Escherichia coli extracellularly - Guangmou Yan; Jianfang Liu; Qiang Ma; Rining Zhu; Zhimin Guo; Chencheng Gao; Shuang Wang; Ling Yu; Jingmin Gu; Dongliang Hu; Wenyu Han; Rui Du; et al. (Antonie van Leeuwenhoek, 2017)

Apigenin attenuates streptozotocin-induced pancreatic β cell damage by its protective effects on cellular antioxidant defense - Ning Wang; Wen Jing Yi; Lu Tan; Jia Hui Zhang; Jiamin Xu; Yi Chen; Mengting Qin; Shuang Yu; Jing Guan; Rui Zhang (In Vitro Cellular & Developmental Biology - Animal, 2017)

Mutations in circularly permuted GTPase family genes AtNOA1/RIF1/SVR10 and BPG2 suppress var2-mediated leaf variegation in Arabidopsis thaliana - Yafei Qi; Jun Zhao; Rui An; Juan Zhang; Shuang Liang; Jingxia Shao; Xiayan Liu; Lijun An; Fei Yu (Photosynthesis Research, 2016)

Matching methods of classic hail echo cores of weather radar - Xue-tao Yu; Xiao-ping Rui; Shuang-xi Fu; Wei Liu (Natural Hazards, 2015)

Clinical Factors Associated With the Diagnosis and Progression of Diabetic Nephropathy - Shuang Liang; Qian Li; Han-Yu Zhu; Jian-Hui Zhou; Rui Ding; Xiang-Mei Chen; Guang-Yan Cai (Cell Biochemistry and Biophysics, 2014)

Valproic acid reduces autophagy and promotes functional recovery after spinal cord injury in rats - Hai-Hu Hao; Li Wang; Zhi-Jian Guo; Lang Bai; Rui-Ping Zhang; Wei-Bing Shuang; Yi-Jia Jia; Jie Wang; Xiao-Yu Li; Qiang Liu (Neuroscience Bulletin, 2013)